Sunitinib for advanced pancreatic neuroendocrine tumors. Issue 12 (December 2011) - Hubner, Richard A; Valle, Juan W
Recent recognition of the high prevalence of neuroendocrine tumors in combination with a sustained failure to improve outcomes for patients with advanced disease has elevated their priority for research and drug development. Sunitinib (SU11248, Sutent; Pfizer Inc. NY, USA) potently inhibits multiple-receptor tyrosine kinases, resulting in antiangiogenic effects. A growing body of evidence indicates angiogenesis is a clinically relevant therapeutic target in pancreatic neuroendocrine tumors, culminating in a Phase III randomized study of sunitinib in patients with advanced progressive pancreatic neuroendocrine tumors. Sunitinib has recently gained regulatory approval as a single agent in this setting, and future studies will investigate most appropriate patient selection, and sequencing and combination with other targeted and cytotoxic agents. Here, we discuss in detail the molecular properties, clinical efficacy and safety of sunitinib in the context of pancreatic neuroendocrine tumors.